HUBUNGAN PERILAKU IBU DALAM PEMBERIAN ASI DAN MP-ASI DENGAN PERTUMBUHAN BADUTA USIA 6-24 BULAN (Studi di Kelurahan Kestalan Kota Surakarta) - Atikah Atikah; R. Djoko Nugroho; Siti Fatimah Pradigdo (Jurnal Kesehatan Masyarakat (Undip), 2017)
Growth is the increasing physical size and structure of the body quantitatively. Growth of toddler measured with units of weight and length and achieving the optimal growth rate is a goal to achieve the survival of children under five. One of the important factors affecting toddler growth is mother's behavior especially in breastfeeding and weaning food. The purpose of this study was to analyze the relationship of mother's behavior in breastfeeding and weaning food to the growth 6-24 months toddler in District Kestalan, Surakarta City. This research is an explanatory research with cross-sectional study design. The population in this study were 41 mothers who had baby aged 6-24 months in January – May 2017, the sample of the study was selected with using total sampling of 41 people. Analysis of data using descriptive and analytic with Rank Spearman test. The results showed the highest percentage of knowledge of high category mother in breastfeeding (78.0%) and weaning food (78.0%), the largest percentage of good mother's attitude in breastfeeding (82.9%) and weaning food (78.0%) and the greatest percentage of good category mother's practice in breastfeeding (80.5%) and weaning food.  (78.0%). There is a relationship of mother's behavior in breastfeeding and weaning food with growth of 6-24 months old with knowledge (p = 0,001), attitude (p = 0,001) and practice (p = 0,001). There was a relationship of mother's behavior in breastfeeding and weaning food to growth of 6-24 months old baby with knowledge (p = 0,001), attitude (p = 0,001) and practice (p = 0,001). It was concluded that there was a correlation between knowledge of mother’s attitude and practice in breastfeeding and weaning food to growth of 6-24 months old toddler. It is suggested that puskesmas officers will be more active and give new innovation when counseling related to breastfeeding and weaning food to mother toddler.